2018
DOI: 10.30723/ijp.v16i38.95
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of superconducting parameters of Bi1.6Pb0.4Sr 2Ca 2Cu 3O10+ δ added with Au nanoparticles

Abstract: Samples of Bi1.6Pb0.4Sr2Ca2Cu3O10+δ superconductor were prepared by solid-state reaction method to study the effects of gold nanoparticles addition to the superconducting system, Nano-Au was introduced by small weight percentages (0.25, 0.50, 0.75, 1.0, and 1.25 weight %). Phase identification and microstructuralcharacterization of the samples were investigated using XRD and SEM. Moreover, DC electrical resistivity as a function of the temperature, critical current density Jc, AC magnetic susceptibility, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The results of X-ray diffraction (XRD) showed that all of the samples examined had an orthorhombic polycrystalline structure, with level of elevation concentration regarding the phase of high temperature. Bi-2223 and numerous Prominent peaks of Bi-2212 at reduced temperatures, as well as the presence of unknown impurity phases, see references [11,12,17]. The atoms may appear to be in two or three different phases if Ni is accidentally swapped with Cu in the original structure.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The results of X-ray diffraction (XRD) showed that all of the samples examined had an orthorhombic polycrystalline structure, with level of elevation concentration regarding the phase of high temperature. Bi-2223 and numerous Prominent peaks of Bi-2212 at reduced temperatures, as well as the presence of unknown impurity phases, see references [11,12,17]. The atoms may appear to be in two or three different phases if Ni is accidentally swapped with Cu in the original structure.…”
Section: Discussion and Resultsmentioning
confidence: 99%